Inter-Ethnic Communication Barriers in Pontianak City - Paramita, Sinta; Carissa, Rose Mita (Jurnal The Messenger, 2018)
This study aims to find out how the expectations of each ethnic group in maintaining the issue of inter-ethnic life harmony in the Province of West Kalimantan, especially in Pontianak City which consists of the majority of the ethnics of Dayak, Malay, and Tionghoa. Multi-ethnic life in Pontianak City often creates various conflicts. This study is a qualitative research using descriptive qualitative method. In this study, the reseachers linked several theories of intercultural communication and identified the communication barriers such as Stereotype, Ethnocentrism, etc. This study found that inter-ethnic conflicts can arise due to the absence of opened mind in facing the differences, the lack of mutual tolerance and mutual respect among ethnic groups. In addition, communication barriers also become one of the factors of the arise of such inter-ethnic conflict.